Analysis Of Inheritance Rights Disputes in Sinarmas Families - Shafira, Shelly Khalimatus; Putri, Sifa Amelia; Ainurohwati, Yessi; Mubarok, Ahmad Zaki (Diponegoro Private Law Review, 2024)
Disputes often occur in society, especially inheritance disputes within the family. One of the cases was a dispute over inheritance rights in the Sinarmas family, where the son of the founder of Sinarmas Group, Freddy Widjaja, felt that it was unfair in his father Eka Tjipta Widjaja's will regarding the distribution of an inheritance worth IDR 737 trillion. Finally, a conflict arose within the family which resulted in a lawsuit from Freddy Widjaja to court. The conflict could be resolved through mediation and deliberation, but the mediation efforts failed and the conflict was resolved and legal action was chosen to resolve the case. This research aims to find out and analyze inheritance rights disputes within the family by describing solutions based on civil law regarding inheritance. The research method used is a normative juridical research method. The data sources used are secondary data sources through websites, books, articles, journals and others.